The Boy Who Harnessed The Wind : creating currents of electricity and hope - Kamkwamba, William. 1987-; Mealer, Bryan (New York: William Morrow, Harper Collions Publishers, 2010)
An enterprising teenager in Malawi builds a windmill from scraps he finds around his village and brings electricity, and a future, to his family.
Keywords: Kamkwamba, William, -- 1987-; Mechanical engineers -- Biography. -- Malawi; Windmills -- Malawi